Advantages of training with an adaptive driving device on a driving simulator compared to training only on the road. (3rd April 2021) - Couture, Mélanie; Vincent, Claude; Gélinas, Isabelle; Routhier, François
Abstract: Purpose: To compare the advantages of training on a driving simulator versus on the road, when learning to drive with new assistive technologies (AT) in individuals with motor impairments. Method: An experimental group (EXP = 16) that trained on a driving simulator was compared to a comparison group (CMP = 16) that received training only on the road. A post-training road test assessed driving performance. Analysis included proportion of participants who successfully completed the on-road driving test, number of training sessions, level of satisfaction, simulator sickness, advantages and discomforts. Results: EXP and CMP were comparable for age (48 ± 17 years), sex (13 M, 3 F), and AT (3 steering wheel knobs with integrated switches, 4 left accelerators, 9 hand controls and steering wheel knobs). No significant difference was observed between groups in the proportion of participants who were found to be fit to drive (EXP: 9/16; CMP: 13/16; p  = 0.126) or in the number of sessions completed (EXP: 4.3; CMP: 3.2; p  = 0.061). For 6 of the 9 satisfaction variables, participants reported being satisfied/very satisfied with training on a simulator with driving assistive technologies 76% to 100% of the time. EXP was satisfied to have been able to use simulator sessions before going on the road (100%). Participants determined to be fit to drive on an on-road test following simulator training showed no significant difficulty continuing with the training. EXP reported temporary discomfort on the simulator during the initial session (88%). Conclusion: Simulators provide some advantages for training drivers with adaptive aids in a safe context. IMPLICATIONS FOR REHABILITATION: Among individuals with motor impairments who used to drive:   All participants reported a high level of satisfaction training on the simulator with assistive technologies. The simulator proved to be an interesting tool for initiating training with new driving AT in a safe environment at no cost to individuals. The few discomforts reported during the first session resolved over time when participants continued with the driving simulator protocol. Occupational therapists noticed that the difficulties observed on the simulator were the same as those observed during on-road testing. The simulator allowed participants to begin to learn how to operate a vehicle with new assistive technology in a safe context.